V4046 Sgr: X-rays from accretion shock. Issue Volume 9:Issue S302(2013) (7th August 2014) - Argiroffi, C.; Maggio, A.; Montmerle, T.; Huenemoerder, D.; Alecian, E.; Audard, M.; Bouvier, J.; Damiani, F.; Donati, J.-F.; Gregory, S.; Güdel, M.; Hussain, G.; et al.
Abstract: We present results of the X-ray monitoring of V4046 Sgr, a close classical T Tauri star binary, with both components accreting material. The 360 ks long XMM observation allowed us to measure the plasma densities at different temperatures, and to check whether and how the density varies with time. We find that plasma at temperatures of 1–4 MK has high densities, and we observe correlated and simultaneous density variations of plasma, probed by O VII and Ne IX triplets. These results strongly indicate that all the inspected He-like triplets are produced by high-density plasma heated in accretion shocks, and located at the base of accretion flows.